2014
DOI: 10.1371/journal.pone.0088877
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D and Incident Statin Induced Myalgia—A Retrospective Cohort Study

Abstract: Background and ObjectivesEvidence is conflicting with regards to the role of vitamin D in statin induced myalgia (SIM). Studies so far have assessed cross-sectional association and were limited by study sample selected predominantly from cardiology clinics. In this retrospective cohort study we assessed the association between vitamin D and SIM and attempted to establish a serum vitamin D cutoff to identify patients at risk for developing SIM.MethodsMedical charts of 5526 consecutive patients from a primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
(38 reference statements)
0
30
0
1
Order By: Relevance
“…In some available studies, low serum concentrations of 25-hydroxyvitamin D (≤ 20 ng/mL) have been associated with myalgia and reduced muscle function [33][34][35][36][37][38][39][40]. Ahmed et al [21] reported that 128 statin-treated patients with myalgia had significantly lower mean serum vit D level than 493 asymptomatic patients (28.6 ± 13.2 vs 34.2 ± 13.8 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some available studies, low serum concentrations of 25-hydroxyvitamin D (≤ 20 ng/mL) have been associated with myalgia and reduced muscle function [33][34][35][36][37][38][39][40]. Ahmed et al [21] reported that 128 statin-treated patients with myalgia had significantly lower mean serum vit D level than 493 asymptomatic patients (28.6 ± 13.2 vs 34.2 ± 13.8 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of vit D levels (as well as its supplementation) in patients with statinassociated myalgia was investigated in several studies [21,[33][34][35][36][37][38]. As a part of a cohort study evaluating the relationship between serum vit D levels and myalgia [21], 82 vit D deficient myalgic patients (vit D level: 20.8 ± 7.1 ng/mL) were prescribed 50,000 units of ergocalciferol weekly for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Recent studies have reported that vitamin D deficiency is associated with a higher prevalence of myalgia induced by statins. 61 In 2014, Shantha et al 62 performed a retrospective study with 5,526 patients followed by a prospective analysis in which the patients were followed up for 7 years. The patients with measured serum vitamin D levels who started treatment with statins were considered as the exposure group.…”
Section: Vitamin D Deficiency and Myalgia Induced By Statinsmentioning
confidence: 99%
“…The authors concluded that low levels of vitamin D were associated with myalgia and that a cutoff level of 15 ng/ mL for vitamin D showed a high accuracy in predicting the emergence of myalgia induced by statins. 62 In 2015, Morioka et al 63 performed a study with 5,907 patients to analyze if the level of vitamin D would modify the association between the use of statin and the emergence of musculoskeletal pain. The authors concluded that the group with vitamin D level below 15 ng/mL and using statins presented an approximately two-fold greater chance of developing musculoskeletal pain than patients who also had vitamin D levels below 15 ng/mL but were not treated with statins.…”
Section: Vitamin D Deficiency and Myalgia Induced By Statinsmentioning
confidence: 99%